Cover Feature: H2 Activation in [FeFe]‐Hydrogenase Cofactor Versus Diiron Dithiolate Models: Factors Underlying the Catalytic Success of Nature and Implications for an Improved Biomimicry (Chem. Eur. J. 5/2019). Issue 5 (20th December 2018) - Arrigoni, Federica; Bertini, Luca; Bruschi, Maurizio; Greco, Claudio; De Gioia, Luca; Zampella, Giuseppe
Abstract : A DFT study on the H2 catalytic oxidation in both the [FeFe]‐H2 ase active site and biomimicry reveals that the origin of the higher performance of nature is due to an enzyme core endowed with both electron‐richness (supporting electron removal) and a single electron‐poor Fe (supporting H2 binding). The key ligand ensuring both features is CN − because of its dual nature as a Lewis π‐acid and a σ‐base. (CN) x ‐Fe y complexes were formerly used in the reverse reaction (H2 formation), but showed undesirable side effects under acidic conditions. However, H2 oxidation requires bases for H + removal. Hence, reconsidering CN − to improve H2 activation sounds like a "back to the future" for the synthetic design. More information can be found in the Full Paper by L. De Gioia, G. Zampella et al. onpage 1227 .